Kontestasi Local Knowledge And Modern Scientific Swine Breeders Biak-Numfor Regency - Pangurian, Mariana Sarlota (Advances in Social Sciences Research Journal, 2018)
The purpose of the study to analyze the existence of local knowledge breeder pigs and its reunion with Modern knowledge in Biak Numfor-. Research methods: this research use the paradigm of Constructivism which discourse and knowledge are seen as social reality. Reality dikontruksi in a given context and social life, is exploratory, theory was born and developed in the field, more emphasis on meaning and value as well as relying on accuracy in the collection of data to uncover the circumstances that Indeed in the field appropriately. The approach used is qualitative. Result of discussion: first, a pig breeder pattern is done mainly by the local population/ethnic population Breeds based local wisdom culture of Biak inherited hereditarylike maintenance, how the selection of the original Pig breeds, how to feeding available in nature, how prevention and treatment with the use of basic materials such as different types of leaves, fruit, bark, seaweed and sea cucumber is local wisdom contained and provided by nature in the amount will never run out. Second, is the pattern of pig breeders are made on the basis of Modern Knowledge. The pattern of these hog farms more done by breeders of pigs originating from outside of New Guinea pig breeders, i.e. from Manado, Batak, Toraja by way of maintenance with the enclosure of the cement, the selection of seed feeding pigs to race, so from the factory or a mixture of bran, remains of food stalls and the ways of prevention and treatment of chemical medicines used comes from the factory with medical or paramedical personnel. Third, is the pattern of kontestasi knowledge at level of local households, local communities, local government and the local market going positive response and the response was negative. Summary: the system of the local community (local societal system) responding to the occurrence of kontestasi between the local knowledge with modern scientific developments in hog farms in Biak-Numfor. The pattern of kontestasi knowledge at level of local households, local communities, local government and the local market going positive response and the response was negative.The most accepted patterns and responded positively to the local community of the whole system of 12 rancher i.e. is the select pattern of the coexistence of 9 second i.e. breeders knowledge takes place when there is a shared presence without mutual influence in the kontestasi between narrative meaning the same breeder will wear both knowledge while 3 breeders choose zero sum game pattern takes place when there is mutually nullify in kontestasi between narrative meaning a breeder would choose use one of the two dominant knowledge.